Data from: Wettability of juvenile plumage as a major cause of mortality threatens endangered Barau’s Petrel - Weimerskirch, Henri; Pinet, Patrick; Dubos, Jerome; Andres, Sylvie; Tourmetz, Julie; Caumes, Christophe; Caceres, Sarah; Riethmuller, Martin; Le Corre, Matthieu (Dryad, 2019)
Seabirds spend most of their life at sea and have to possess a waterproof
plumage to be able to sit on water for extended periods. We tracked
juvenile Barau’s petrels for the first time, when they leave their birth
colony and found that half of the transmitters stopped soon after they
first landed on the water off Réunion Island. We suspected from
observation at sea that birds may have problems with the waterproofness of
their plumage. Therefore during the next season we set up a simple
protocol to assess waterproofness of the plumage of the birds just before
they fledge. This protocol is based on the calculation of a wettability
index expressed as the mass of water logged in the plumage after
simulating the bird sitting on the sea surface. We found that at least one
third of chicks ready to fledge gained more than 4 g of water in 20 sec,
indicating that plumage was not waterproof. Within a sample of birds
having fledged and before reaching the sea surface, a similar proportion
of birds had their plumage not waterproof. For the birds tracked, only
those with an index indicating a waterproof plumage successfully dispersed
after their first touch on the sea surface. We provide evidence of a
possible major cause of mortality of juvenile seabirds that has not been
described previously in wild seabirds, but could exist in other species.
This issue may be a major cause of threat to the endangered Barau’s
petrel.
all location juvenile Barau's petrels weimerskirch
Keywords: Pterodroma baraui; Tracking Data; plumage structure